Tool and die making troubleshooter - Leed, Richard M. (Society of Manufacturing Engineers, 2002)
"The book contains hands-on information, valuable tooling tips, and procedural recommendations regarding the selection, processing, and use of materials. This comprehensive reference is for anyone working with the selection, application, and use of cast irons, cast steels, wrought tooling sheets, and aluminum and stainless steels. The subjects of basic metallurgy, heat treating, machining, grinding, electrical discharge machining, welding, quality, wear enhancements, surface coatings, and treatments for tools and dies have been carefully organized and presented for quick reference."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.